Communicative intent and communicative strategies of spoken discourse by using social stories among autism spectrum disorder children in Malaysia - Amirrudin, Suraya (2020)
It is prevailing that ASD children often seem to have difficulty with social, cognitive and language processes. Since autism is related to language deficit, many previous scholars in the field have linked the study of autism with language functions or discourse. Hence, it is long known that children with ASD respond to interventions that target their specific skills and behaviour and numerous studies have demonstrated the positive effects of early intervention on language development for the majority of ASD children. Likewise, in this study, the communicative intent of the spoken discourse is examined by using social stories through the identification of the elements of discourse in utterances among ASD children. Other than that, the investigation is further conducted to examine the communicative strategies employed by the ASD respondents. Following that, the communicative intent and communicative strategies of the spoken discourses produced by the low, medium and high functioning ASD children were compared. The current study uses qualitative data to provide details to the research objectives, and a case study method design is utilised for the collection and analysis of the data. The school chosen for the data collection is a primary school in Seri Kembangan. There are four female and nine male ASD children selected as the sample for the study. The age is ranged from 9 to 11 years old. As for the instruments, the study utilises two main instruments; social stories and semi-structured interview questions. On top of that, the participant observations are also being conducted. There are three different social stories (Visiting atuk and nenek in Kampung, Being Kind to Animals and Helping My Family) narrated to the respondents. The duration for data collection is long enough to see the progress of the 13 respondents. The data is transcribed manually and later confirmed by using the Atlas. ti8 software. Nevertheless, to explain more about this phenomenon, the current research employs two theories; Discourse Analysis Theory (Normaliza Abd Rahim, 2019) and one taxonomy- Tarone Taxonomy for Communicative Strategies (1980). Above all, the findings of the study revealed that the 13 respondents displayed seven communicative intent signals and their spoken utterances subscribed to the three elements (content, context and assumption) mentioned in the discourse theory. The aspects, in theory, have helped the ASD respondents to be able to understand the content and context of the social stories. Furthermore, in the baseline condition, the ASD respondents also demonstrated a stable trend in all elements under the communicative strategies; paraphrase (approximation, word coinage, circumlocution), borrowing (literal translation, language switch, appeal for assistance and mime) and avoidance (topic avoidance and message abandonment). In the end, the current study is also succeeded in comparing the discourses of the ASD children according to their categories; LFA, MFA and HFA and coming up with the repertoire (list of utterances and gestures). For the communicative intent, two similarities were found; firstly, all the three groups; LFA, MFA and HFA demonstrated the seven communicative intent signals and secondly, their utterances matched with the elements in the Discourse Analysis Theory (2019). Moving on to the communicative strategies, all strategies were engaged by the 13 ASD respondents and they were different in terms of the degree on how much the engagement was. All these were acquired through their understanding from the social stories. All in all, there is no magic formula for teaching special educational needs students, especially autism. The knowledge that is obtained here about utterances, communicative intent, communicative strategies and social stories could be used consistently and consciously to obtain greater effects for the future.